Oleophobic interaction mediated slippery organogels with ameliorated mechanical performance and satisfactory fouling-resistance. (10th September 2022) - Zeng, Liangpeng; Cui, Hongyuan; Peng, Huilan; Sun, Xiaohang; Liu, Yi; Huang, Jingliang; Lin, Xinxing; Guo, Hui; Li, Wei-Hua
Highlights: A simple and effective method to prepare organogels with reinforced mechanical performance and surface lubricant ability has been developed. The novel organogels demonstrate high stiffness, strength, and toughness, far beyond the conventional organogels. The reinforced organogels exhibit satisfactory lubricant ability and antifouling performance, bringing in 4 to 9-fold reduction of protein and bacteria adhesion. This strategy to toughening of organogels can be applied to various systems, which may endow them with versatile practical applications in the future. Abstract: Owing to their inherent semi-solid property and lubricant ability, organogels manifest various unique characteristics and serve as promising candidates for antifouling. However, the poor mechanical properties of organogels often limit their practical applications. Herein, we report a simple and effective method to prepare organogels with reinforced mechanical performance and surface lubricant ability with the synergistic roles played by oleophobic and oleophilic chains. The rigid oleophobic chains have a poor affinity to lubricating solvent, which gives rise to high oleophobic interactions between polymer networks; the soft oleophilic chains possess a high affinity to the low surface energy solvent, which lead to high solvent content to maintain the satisfactory lubricant capacity. The organogel of oleophobic methyl methacrylate (MMA) and oleophilic lauryl methacrylate (LMA) is chosen as a representative example to illustrate this concept. With the optimal composition, the as-prepared organogels offer satisfactory tensile fracture stress, fracture strain, Young's modulus, toughness, and tearing fracture energy of 480 kPa, 550%, 202 kPa, 1.14 MJ m −3, and 5.14 kJ m −2, respectively, which are far beyond the classical PLMA organogels. Furthermore, the biofouling resistance tests demonstrate 4 to 9-fold reduction of protein and bacteria adhesion on the reinforced organogels surface in comparison to the glass substrate and solvent-free dry organogels. This simple and effective approach to toughen organogels, we hope, can be applied in various fields with different practical functional requirements in the future. Abstract : Image, graphical abstract